The maximum number of node retrieval in axillary lymph node dissection in breast cancer patient (84/84); high nodal burden in breast cancer female patient: a case report and review of literature - Khalil, Mahmoud H.; Sharif, Ragab A.; Tahoun, Neveen; Shehata, Ahmed A. (International Surgery Journal, 2025)
We describe the case of a 41 years old female presented with right breast retro areolar painless hard mass accompanied by nipple retraction. After initial clinical assessment, further clinical radiological investigations, bilateral sonomamography imaging showed an ill-defined focal hypo echoic heterogenicity at the retro areolar region measures about 40×26 mm. Another two ill-defined hypo echoic soft tissue masses at upper inner quadrant measures about 17×16 mm and 13×11 mm. With enlarged right axillary lymph node about 20 mm in size, thickened cortex and still preserved hilum (BIRAD Ⅴ lesions). The diagnostic image guided multiple core biopsies confirmed the multicentric invasive breast cancer and molecular subtyping as Luminal B breast cancer stage Ⅱb. Whole body computed tomography (CT) as a Metastatic work was free. After the discussion among the Breast cancer Multi-disciplinary team (MDT) members and the patient, the final decision was to do surgery first in the form of right modified radical mastectomy respecting the patient desire for this choice loco regional control first - then to continue her adjuvant treatment according to the final histopathological reporting. The surprise is the unexpected this extreme number of axillary lymph nodes retrieval (84/84) after the final histopathological examination of the specimen. We did not find this extreme number of axillary lymph nodes retrieval "84" before in the literature at all regarding breast cancer management by ALND.